Parent Child Conversations Regarding the Movie Finding Dory - Greer, Alexandra (My University, 2018)
Children are able to recall a past event by the age of three (Bauer, 2007). The ability to recall past events is influenced by many factors, such as parent-child memory conversations (Fivush & Fromhoff, 1988; Fivush, Haden & Reese, 2006) and children's development of language (Simcock & Hayne, 2002, 2003). Another factor that contributes to children's memory skills is their conversations with their parents about past events. Conversational skills are developed over a period of time and through a variety of sources. Children learn how to communicate from their parents, a skill which develops sometime between the ages of three to five (Fivush, 2007). The style of conversation the parent uses plays a large role in not only how their children communicate, but also in how their personality develops (Buckner & Fivush; 1998). Parent-child memory conversations shape the way children recall and actually help to "teach" children how to remember (Fivush & Fromhoff, 1988).
Keywords: child psychology; Memory in children; Children's films; Motion Pictures